Ekonomiczno-finansowe instrumenty gospodarczego rozwoju lokalnego - Zawora, Jolanta (Wydawnictwo Uniwersytetu Rzeszowskiego, 2016)
Law states that the most important tasks related to the development of the particular region are performed by the municipality. This article aims to identify tools at the disposal of municipal government in the process of local development, particularly financial methods of promoting the economic growth. The analysis includes polish communities by characterizing the range of investment activities carried out by these units. Municipalities and cities with poviat status had the largest share in realization of the investment of local government (in total over 70%). Most of funds for investments were dispensed in the budgets of municipalities in 2009–2011. The level of government investment decreased significantly since 2012.
Keywords: local development; tools to support local development; municipal government; local government investments